Art, psychotherapy, and psychosis - Killick, Katherine; Schaverien, Joy, 1943- (Routledge, 1997)
"Art, Psychotherapy and Psychosis reveals the unique role of art therapy in the treatment of psychosis. Illustrating their contributions with clinical material and artwork created by clients, experienced practitioners describe their work in a variety of settings. Writing from different theoretical standpoints they reflect the current creative diversity within the profession and its links with psychotherapy, psychoanalysis, analytical psychology and psychiatry." "Art, Psychotherapy and Psychosis extends existing theory, develops analytical approaches in art psychotherapy and offers innovative perspectives for students and practitioners on the treatment of borderline states as well as psychosis."--Jacket